Validity And Reliability Of The Self Administered MemTrax Test In Students - Rizki Amelia Sinensis; Meida Sofyana; Jajar Setiawan; Zaenal Muttaqien Sofro; Wahyudin Wahyudin (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Background: Students have serious challenges when they enter their first year at university. Stress can cause impaired cognitive function. The large number of activities, school time and technology have an influence on sleep activities which intersect with sleep physiology. The MemTrax test is an online computerized test with measure memory performance. The aim of this research is to determine the validity of the self administered MemTrax Test in measuring RT and PC compared to the standard MemTrax Test and to determine the reliability of the self administered MemTrax Test in measuring RT and PC. Method: This research is an observational study by testing the construct validity and reliability of the MemTrax Mandiri Test. The sample in this study was 54 students aged 19-24 years who were the validity sample, and 41 students aged 18-25 years who were the reliability sample. Validity data analysis used correlation analysis between the RT and PC of the MemTrax Test and the self administered MemTrax Test. Reliability analysis uses test retest reliability using the Intraclass Correlation Coefficient. Results: The RT results of the self administered MemTrax Test with the MemTrax Test have a significant relationship with a significance value of 0.00 and a strong correlation strength value of 0.658, and the value is not correlated with PC. For reliability, it was found that the reaction time results of the self administered MemTrax Test had a moderate reliability value, namely 0.646, while the reliability value for percent correct for the self administered MemTrax Test had a low value, namely 0.585. Conclusion: The self administered MemTrax test is not valid, this is proven by the RT results which are correlated, but the PC is not correlated. The self administered MemTrax test is not yet reliable, as evidenced by the results of moderately correlated RT and weakly correlated PC, so the self administered MemTrax test cannot be used as a cognitive function examination tool at this time. Keywords: Online memory test, Self administered memory test, Cognitive Function, Reaction Time, Percent Correct